Why don't some women attend antenatal and postnatal care services?: a qualitative study of community members' perspectives in Garut, Sukabumi and Ciamis districts of West Java Province, Indonesia - Heywood Peter; Hunter Cynthia L; Titaley Christiana R; Dibley Michael J (BMC, 2010)
Abstract Background Antenatal, delivery and postnatal care services are amongst the recommended interventions aimed at preventing maternal and newborn deaths worldwide. West Java is one of the provinces of Java Island in Indonesia with a high proportion of home deliveries, a low attendance of four antenatal services and a low postnatal care uptake. This paper aims to explore community members' perspectives on antenatal and postnatal care services, including reasons for using or not using these services, the services received during antenatal and postnatal care, and cultural practices during antenatal and postnatal periods in Garut, Sukabumi and Ciamis districts of West Java province. Methods A qualitative study was conducted from March to July 2009 in six villages in three districts of West Java province. Twenty focus group discussions (FGDs) and 165 in-depth interviews were carried out involving a total of 295 respondents. The guidelines for FGDs and in-depth interviews included the topics of community experiences with antenatal and postnatal care services, reasons for not attending the services, and cultural practices during antenatal and postnatal periods. Results Our study found that the main reason women attended antenatal and postnatal care services was to ensure the safe health of both mother and infant. Financial difficulty emerged as the major issue among women who did not fulfil the minimum requirements of four antenatal care services or two postnatal care services within the first month after delivery. This was related to the cost of health services, transportation costs, or both. In remote areas, the limited availability of health services was also a problem, especially if the village midwife frequently travelled out of the village. The distances from health facilities, in addition to poor road conditions were major concerns, particularly for those living in remote areas. Lack of community awareness about the importance of these services was also found, as some community members perceived health services to be necessary only if obstetric complications occurred. The services of traditional birth attendants for antenatal, delivery, and postnatal care were widely used, and their roles in maternal and child care were considered vital by some community members. Conclusions It is important that public health strategies take into account the availability, affordability and accessibility of health services. Poverty alleviation strategies will help financially deprived communities to use antenatal and postnatal health services. This study also demonstrated the importance of health promotion programs for increasing community awareness about the necessity of antenatal and postnatal services.